Review of Cr(VI) environmental practices in the chromite mining and smelting industry – Relevance to development of the Ring of Fire, Canada. (1st November 2017) - Beukes, J.P.; du Preez, S.P.; van Zyl, P.G.; Paktunc, D.; Fabritius, T.; Päätalo, M.; Cramer, M.
Abstract: During stainless steel production, new chromium units are obtained from ferrochrome, a relatively crude alloy produced from chromite ore. Large chromite reserves have recently been discovered in the so-called Ring of Fire, Canada. Due to the strategic importance of uninterrupted stainless steel production in North America, it is highly likely that these reserves will be exploited in the foreseeable future. However, the Ring of Fire is located in an area that forms part of the largest peatland in the world, as well as the traditional territories of several First Nations (indigenous American communities), which highlights the environmental and social sensitive nature of the intended developments. In this review, relevant mining and/or smelting processes were considered within the context of possible prevention and mitigation of hexavalent chromium, Cr(VI), formation, and the treatment of possible Cr(VI) containing waste materials. Cr(VI) is classified as a carcinogen and it has several negative environmental impacts. Prior to commencing chromite mining in the Ring of Fire, baseline studies should be undertaken to determine the possible natural occurrence of Cr(VI) in soils, untreated chromite ore and surface/groundwater, as well as sources thereof. During mining and ore processing, dry milling was identified as the only process step with the potential to generate Cr(VI); therefore, it should be avoided. Instead, wet milling should be used. Assessments of all process steps associated with conventional ferrochrome production indicated that smelting will lead to the formation of unintended small amounts of Cr(VI) (mg.kg −1 concentration range), irrespective of the technology applied. However, this review proved that it will be possible to produce ferrochrome without causing occupational/community health issues related to Cr(VI), as well as environmental pollution, if appropriate preventative and mitigation measures are applied. Apart from Cr(VI) related considerations, it is acknowledged that factors such as physical and chemical characteristics of the ore, capital and operational costs, specific electricity consumption, carbon footprint, and availability of expertise will determine what process options will be implemented. Highlights: It is likely that Ring of Fire chromite reserves in Canada will be exploited. Ferrochrome smelting will lead to the formation of small amounts of Cr(VI). Appropriate preventative and mitigation measures need to be applied. The review proved that it is possible to prevent and/or limit Cr(VI) pollution.